Low-Intensity Pulsed Ultrasound and Halo Immobilization Is an Effective Treatment for Nonunion Following Traumatic Spondylolisthesis of the Axis - Oda, Kohtaroh; Ohba, Tetsuro; Ebata, Shigeto; Haro, Hirotaka (Journal of Neurological Surgery Reports, 2017)
This case report describes a unique case involving traumatic spondylolisthesis of the axis that resulted in nonunion, angulation, and displacement after conservative treatment with a cervical collar, but which was successfully achieved union with halo immobilization and low-intensity pulsed ultrasound (LIPUS). Halo immobilization of a traumatic spondylolisthesis in a 20-year-old patient, that previously failed to improve after wearing a cervical collar for 3 months, was immediately followed by treatment with a LIPUS device (SAFHS 4000J; Teijin Pharma, Tokyo, Japan) 20 minutes once daily to the right and left fracture sites which were located using fluoroscopic guidance. Radiographs and computed tomography showed conclusive evidence of bone union after 10 weeks of treatment with halo immobilization. No adverse events were observed. To the best of our knowledge, this is the first report describing that the combination of halo immobilization and LIPUS therapy might be a safe, effective, and feasible method by which to treat cervical spine fractures.
Keywords: nonunion; traumatic spondylolisthesis of the axis; low-intensity pulsed ultrasound; bone union